-7x-12(x+7)=-2(9x+5)

Simple and best practice solution for -7x-12(x+7)=-2(9x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-12(x+7)=-2(9x+5) equation:


Simplifying
-7x + -12(x + 7) = -2(9x + 5)

Reorder the terms:
-7x + -12(7 + x) = -2(9x + 5)
-7x + (7 * -12 + x * -12) = -2(9x + 5)
-7x + (-84 + -12x) = -2(9x + 5)

Reorder the terms:
-84 + -7x + -12x = -2(9x + 5)

Combine like terms: -7x + -12x = -19x
-84 + -19x = -2(9x + 5)

Reorder the terms:
-84 + -19x = -2(5 + 9x)
-84 + -19x = (5 * -2 + 9x * -2)
-84 + -19x = (-10 + -18x)

Solving
-84 + -19x = -10 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-84 + -19x + 18x = -10 + -18x + 18x

Combine like terms: -19x + 18x = -1x
-84 + -1x = -10 + -18x + 18x

Combine like terms: -18x + 18x = 0
-84 + -1x = -10 + 0
-84 + -1x = -10

Add '84' to each side of the equation.
-84 + 84 + -1x = -10 + 84

Combine like terms: -84 + 84 = 0
0 + -1x = -10 + 84
-1x = -10 + 84

Combine like terms: -10 + 84 = 74
-1x = 74

Divide each side by '-1'.
x = -74

Simplifying
x = -74

See similar equations:

| 4(5x-4)-19x=1 | | f+f+f+f+f=0 | | 2m*3=0 | | -9x-6(x+8)=-2(7x+2) | | 46+567777651524=12 | | 46+567777651524= | | -4x=104 | | 5x+13=2x+97 | | x=56475444578-145666 | | 101-7x=38x+21 | | 47-9t=7-4t | | 129-4x=6x+9 | | 14x+14=27 | | 3x+10=-74-9x | | 98-2x=5x+7 | | -28-2=7-9x | | 3x+5x+x= | | 6x+40=13x-23 | | (11s+r)(-7r+s)= | | (X^2+1)(X+9)= | | 5x-29=31 | | (100+X)(X-100)= | | (x+y)(z+y)= | | (x+5)(y+10)= | | 72-7j=72 | | (x-6)(x+9)= | | 6x-5y=8 | | (m^2-7m-6)(7m^2-3m-7)= | | 4-5x=9x+18 | | 3-x=9-3x | | 14-6b=4b+34 | | 9-3s=4s+30 |

Equations solver categories